Pengembangan Rumah Baca di Pedesaan Dengan Fleming Model (VAK) - Nunik Hariyani; Veny Ari Sejati (Universitas Merdeka Madiun, 2019)
The reading garden as a place for learning activities is still quiet of enthusiasts and visitors. In fact, the reading park should be able to become a supporter to increase new literary characters. Taman Baca must support the out-of-school program curriculum. The village reading park must act as a learning tool for the community. The reading garden must be able to be a source of information that provides resources from books and other reading materials. Village reading parks should have reference materials for learning and academic activities. The reading garden must also be a source of entertainment (recreation) that provides recreational reading material to take advantage of leisure time. The activities carried out in the form of socialization and mentoring of learning in Taman Baca Masyarakat (TBM). This program aims to foster reading interest and a love of reading in rural children, thus enriching the learning experience for citizens and adding insight into science and technology. The socialization activities in TBM are about five Basic Principles of Literacy Development and Implementation. While the assistance activities are in the form of applying learning styles with the Fleming Model.